The generation, recognition and legitimation of novelty - Cattani, Gino; Deichmann, Dirk; Ferriani, Simone (Emerald Publishing Limited, 2022)
This volume brings together researchers from a diverse array of academic disciplines - including sociology, organization theory, strategy and psychology - to address the question of what organizations can do to better recognize novel ideas and support their proponents in implementing those ideas. The contributors draw from different theoretical perspectives and empirical papers use both qualitative and/or quantitative methods in their analysis. All contributions speak to a common set of phenomena at the intersection of creativity, innovation, and social evaluation in a variety of cultural fields. In the first section of the volume - searching for novelty - the papers discuss different conceptualizations of novelty and examine the conditions that foster the creation of new ideas or product offerings. In the second section of the volume - seeing novelty - the papers discuss how novelty is evaluated and recognized both within and outside organizations. Papers in the third and final section - sustaining novelty - explore how these evaluations affect the support that novelty receives in its journey to gain legitimacy. Setting an agenda for a more holistic theory on the emergence, evaluation, and legitimation of novelty, this volume showcases how novelty generation, recognition, and legitimation correspond to distinct phases of the journey of novelty, from the moment it makes its appearance in the world to the moment it takes root and propagates.
Includes index.
Keywords: Organizational behavior -- Social aspects.; Group decision making -- Social aspects.; Originality.; Social Science -- Sociology -- General.; Sociology.; elektronické knihy; electronic books